Empirical Evidence on Contract Farming in Northern Nigeria: Case Study of Tomato Production - Kutawa, Iro Ibrahim (Asian Journal of Agriculture and Rural Development, 2021)
This study contributes to the scarce empirical evidence on contract farming in Northern Nigeria using a case study of tomato production. Using data from five Local Government Areas of Kano State in Northern Nigeria, a total of 116 tomato contract farmers and 84 non contract farmers were selected. The econometric result indicated that there was a high level of participation in contract farming. Participation in contract farming generated desirable causal effects on transaction costs, productivity, tomato income, total household income and poverty status of the farmers and this implies that the contract farming arrangement is very appealing to the farmers currently engaged in contract farming. The major factors that swayed the farmers’ decision to engage in contract farming were education, farm size and extension indicating that these variables are key policy variables that could be leveraged to influence participation in contract farming in the study area. The study may give detailed information on how contract and non-contract tomato production is currently functioning in northern Nigeria.